Judicialization of administrative measures to tackle the COVID-19 pandemic in Brazil - Figueiredo, Iara Veloso Oliveira (2020)
This article studied the judicialization lawsuits related to the pandemic of the new coronavirus, within the scope of Administrative Law. The cases that reached the Brazilian Federal Supreme Court (FSC), available at the “Painel de Ações COVID-19”, were analyzed, as well as a sample of the cases that reached the state courts, obtained through journalistic reports, consolidated on the " Consultor Jurídico" website. Descriptive analysis and content analysis techniques were used, in the thematic mode, for both sources of information. The following variables were analyzed: procedural classes groups, procedural classes, main subject, notification date, time until the first decision, decisions, decisions groups, and total of cases archived remotely. Near 34% of the actions referred to the flexibilization or tightening of free movement, restrictive measures on and the opening of commerce and services, and another 34% referred to budgeting issues, mainly dealing with the suspension of state debts and untying resources to combat the pandemic. The median time until the first decision made by the FSCwas less than five days for all categories. The judicialization of COVID-19 pointed out already known flaws in public health and social policies in Brazil, and it can encourage a lot of actions, both by the Legislative and the Executive, to mitigate these problems. This article demonstrates the importance of observing the responses brought by the judicialization, and of the dialogue between the three powers, to deal with the demands of the pandemic better and with several other demands of society.